Impaired left ventricular function as a predictive factor for mid-term survival in octogenarians after primary coronary artery bypass surgery (Swiss Medical Weekly, 2012)
BACKGROUND: The impact of preoperative impaired left ventricular ejection fraction (EF) in octogenarians following coronary bypass surgery on short-term survival was evaluated in this study. METHODS: A total of 147 octogenarians (mean age 82.1 ± 1.9 years) with coronary artery diseases underwent elective coronary artery bypass graft between January 2000 and December 2009. Patients were stratified into: Group I (n = 59) with EF >50%, Group II (n = 59) with 50% > EF >30% and in Group III (n = 29) with 30% > EF. RESULTS: There was no difference among the three groups regarding incidence of COPD, renal failure, congestive heart failure, diabetes, and preoperative cerebrovascular events. Postoperative atrial fibrillation was the sole independent predictive factor for in-hospital mortality (odds ratio (OR), 18.1); this was 8.5% in Group I, 15.3% in Group II and 10.3% in Group III. Independent predictive factors for mortality during follow up were: decrease of EF during follow-up for more that 5% (OR, 5.2), usage of left internal mammary artery as free graft (OR, 18.1), and EF in follow-up lower than 40% (OR, 4.8). CONCLUSIONS: The results herein suggest acceptable in-hospital as well short-term mortality in octogenarians with impaired EF following coronary artery bypass grafting (CABG) and are comparable to recent literature where the mortality of younger patients was up to 15% and short-term mortality up to 40%, respectively. Accordingly, we can also state that in an octogenarian cohort with impaired EF, CABG is a viable treatment with acceptable mortality.